Real-time individual benefit from social interactions before and during the lockdown: the crucial role of personality, neurobiology and genes - Monninger, Maximilian; Aggensteiner, Pascal; Pollok, Tania; Reinhard, Iris; Hall, Alisha S. M.; Zillich, Lea; Streit, Fabian; Witt, Stephanie; Reichert, Markus; Ebner-Priemer, Ulrich; Meyer-Lindenberg, Andreas; Tost, Heike; et al. (Translational Psychiatry, 2022)
Social integration is a major resilience factor for staying healthy. However, the COVID-19-pandemic led to unprecedented restrictions in social life. The consequences of these social lockdowns on momentary well-being are yet not fully understood. We investigated the affective benefit from social interactions in a longitudinal birth cohort. We used two real-time, real-life ecological momentary assessments once before and once during the initial lockdown of the pandemic (N = 70 participants; n~6800 observations) capturing the protective role of social interactions on well-being. Moreover, we used a multimethod approach to analyze ecological assessment data with individual risk and resilience factors, which are promising moderators in the relationship of social behavior, stress reactivity, and affective states (i.e., amygdala volume, neuroticism, polygenic risk for schizophrenia). Social contacts were linked to higher positive affect both during normal times and during the COVID-19-pandemic (beta coefficient = 0.1035), highlighting the beneficial role of social embedding. Interestingly, this relationship was differentially moderated by individual risk and resilience factors. In detail, participants with a larger left amygdala volume (beta coefficient = −0.0793) and higher neuroticism (beta coefficient = −0.0958) exhibited an affective benefit from more social interactions prior to the pandemic. This pattern changed during the pandemic with participants with smaller amygdala volumes and lower neurotic traits showing an affective gain during the pandemic. Moreover, participants with low genetic risk for schizophrenia showed an affective benefit (beta coefficient = −0.0528) from social interactions irrespective of the time point. Our results highlight the protective role of social integration on momentary well-being. Thereby, we offer new insights into how this relationship is differently affected by a person’s neurobiology, personality, and genes under adverse circumstances.